Long-term neurologic and cognitive outcome and quality of life in adults after pneumococcal meningitis. (October 2020) - Kloek, A.T.; Brouwer, M.C.; Schmand, B.; Tanck, M.W.T.; van de Beek, D.
Abstract: Objectives: To perform a cross-sectional cohort study on long-term neurologic, cognitive and quality-of-life outcome in adults surviving pneumococcal meningitis. Methods: Adult survivors of community-acquired pneumococcal meningitis from a Dutch nationwide prospective cohort study were evaluated 1 to 5 years after acute illness. The control group consisted of partners or proxies of patients. Neurologic examination was performed and cognitive domains were tested with the Vienna Test System Cognitive Basic Assessment Test set (VTS COGBAT). The Research and Development (RAND)-36 and adapted Cognitive and Emotional Consequences of Stroke (CLCE)-24 questionnaires assessed perceived cognitive functioning and quality of life. Differences between group scores were tested with multivariate analyses of variance. Results: A total of 80 pneumococcal meningitis patients and 69 controls were evaluated. After a median of 2 years (interquartile range, 2–3) after acute illness, 27 (34%) of 79 patients had persistent neurologic sequelae, most commonly hearing loss (21/79, 27%). On overall neuropsychologic evaluation, patients performed worse than the controls (MANCOVA; p 0.008), with alertness ( z score −0.33, p 0.011) and cognitive flexibility ( z score −0.33, p 0.027) as the most affected domains. Cognitive impairment was present in 11 (14%) of 79 patients. CLCE-24 questionnaires revealed cognitive impairment on all domains, most commonly for cognitive speed (53/75, 71%), attention (45/75, 60%) and memory (46/75, 61%). Patients had lower quality-of-life scores than controls (item physical functioning, (median) patients vs. controls, 80 vs. 95, p < 0.001; social functioning, (median) 81 vs. 100, p 0.003; perceived health, (mean) 59 vs. 70, p 0.005), which correlated with cognitive complaints ( R  = 0.66, p < 0.001). Conclusions: Adults after pneumococcal meningitis are at high risk of long-term neurologic and neuropsychologic deficits impairing daily life activities and quality of life.